Obstacles to EU enlargement: the classical community method and the prospects for a wider Europe. - PRESTON, Christopher (1995)
Examines the five principles on which the 'classical' Community method of enlargement is based. Argues that the recently concluded EFTA enlargement is likely to be the last 'classical' enlargement, and that in future a more radical approach will have to be developed if the goal of a genuinely pan-European Union is to be realized.